Glimpses of Tibetan divination: past and present - Maurer, Petra; Rossi, Donatella; Scheuermann, Rolf (Prognostication in history, 2019)
A case of prophecy in post-imperial Tibet / Per Kvœrne -- Three dice, four faces, and sixty-four combinations : early Tibetan dice divination by the numbers / Brandon Dotson -- A preliminary analysis of old Tibetan dice divination texts / Ai Nishida -- Divinations Padampa did or did not do, or did or did not write / Dan Martin -- Landscaping time, timing landscapes : the role of time in the sa dpyad tradition / Petra Maurer -- Signs and portents in nature and in dreams : what they mean and what can be done about them / Charles Ramble -- Identifying the magical displays of the lords of the world : the oneiromancy of the gSal byed byang bu / Donatella Rossi -- Vibhūticandra's Svapnohana and the examination of dreams / Rolf Scheuermann -- Prognosis, prophylaxis, and trumps : comparative remarks on several common forms of Tibetan cleromancy / Alexander Smith -- The role of Lamyn Gegeen Blo bzang bstan 'dzin rgyal mtshan in the dissemination of Tibetan astrology, divination and prognostication in Mongolia / Agata Bareja-Starzynska.